Genetic mechanism for the stage- and tissue-specific regulation of steroid triggered programmed cell death in Drosophila. - Lee, C.Y.; Simon, C.R.; Woodard, C.T.; Baehrecke, E.H. (Developmental Biology, 2002)
Steroid hormones trigger a wide variety of cell-specific responses during animal development, but the mechanisms by which these systemic signals specify either cell division, differentiation, morphogenesis or death remain uncertain. Here, we analyze the function of the steroid-regulated genes betaFTZ-F1, BR-C, E74A, and E93 during salivary gland programmed cell death. While mutations in the betaFTZ-F1, BR-C, E74A, and E93 genes prevent destruction of salivary glands, only betaFTZ-F1 is required for DNA fragmentation. Analyses of BR-C, E74A, and E93 loss-of-function mutants indicate that these genes regulate stage-specific transcription of the rpr, hid, ark, dronc, and crq cell death genes. Ectopic expression of betaFTZ-F1 is sufficient to trigger premature cell death of larval salivary glands and ectopic transcription of the rpr, dronc, and crq cell death genes that normally precedes salivary gland cell death. The E93 gene is necessary for ectopic salivary gland cell destruction, and ectopic rpr, dronc, and crq transcription, that is induced by expression of betaFTZ-F1. Together, these observations indicate that betaFTZ-F1 regulates the timing of hormone-induced cell responses, while E93 functions to specify programmed cell death.